Spaceflight associated neuro-ocular syndrome: connections with terrestrial eye and brain disorders - Joe, Brenna (Frontiers in Ophthalmology, 2024)
Spaceflight Associated Neuro-ocular Syndrome (SANS) is a series of findings found in astronauts who have experienced long-duration spaceflight. It is characterized by neuro-ocular changes that may irreversibly alter vision and increase the risk for the development of terrestrial eye and brain disorders. Theories regarding its etiology and countermeasures to combat the findings seen continue to evolve. There is currently no direct treatment for SANS. Traditional Chinese Medicine (TCM) modalities have been used to treat eye and brain disorders on Earth that are pathogenically similar to SANS, therefore, TCM may be able to target corresponding pathology in astronauts, prevent and mitigate SANS findings, and decrease the risk for future development of disorders. This paper intends to discuss pathological similarities between SANS and terrestrial eye and brain disorders and how TCM has been used to treat those disorders.